2021
DOI: 10.1021/acs.inorgchem.1c02349
|View full text |Cite
|
Sign up to set email alerts
|

The Alkylaluminate/Gallate Trap: Metalation of Benzene by Heterobimetallic Yttrocene Complexes [Cp*2Y(MMe3R)] (M = Al, Ga)

Abstract: Yttrocene derivatives [Cp* 2 Y(MMe 4 )] (Cp* = C 5 Me 5 ; M = Al, Ga) and Cp* 2 Y[Me 3 Al{B(NDippCH) 2 }] (Dipp = C 6 H 3 iPr 2 -2,6) deprotonate benzene at elevated temperatures via the release of methane. The formation of [Cp* 2 Y(Me 2 MPh 2 )] (M = Al, Ga), Cp* 2 Y(MPh 4 ) (M = Al, Ga), Cp* 2 Y[Me 2 AlPh{B(NDippCH) 2 }], and Cp* 2 Y[AlPh 3 {B(NDippCH) 2 }] can be controlled via the temperature applied. The activation temperature and formation of the coordinatively unsaturated "reactive" [Cp* 2 YMe] strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 99 publications
0
4
0
2
Order By: Relevance
“…Alternatively, a transiently formed Sm III − i Bu might deprotonate toluene [44] and benzyl/isobutyl heteroaluminato displacement forced by the donor solvent. For further comparison, it has been previously shown that the alkylaluminate complex [(C 5 Me 5 ) 2 Y(AlMe 4 )] activates benzene and toluene forming phenyl‐incorporated heteroaluminato moieties, which can be displaced by a donor solvent like THF [45] . Although we did not succeed in fully characterizing compound 5 , mainly because NMR spectroscopy was not definitive due to the paramagnetic nature of divalent samarium, the solid‐state structure of 5 gives evidence of ligand exchange as a scenario that might be favored over oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, a transiently formed Sm III − i Bu might deprotonate toluene [44] and benzyl/isobutyl heteroaluminato displacement forced by the donor solvent. For further comparison, it has been previously shown that the alkylaluminate complex [(C 5 Me 5 ) 2 Y(AlMe 4 )] activates benzene and toluene forming phenyl‐incorporated heteroaluminato moieties, which can be displaced by a donor solvent like THF [45] . Although we did not succeed in fully characterizing compound 5 , mainly because NMR spectroscopy was not definitive due to the paramagnetic nature of divalent samarium, the solid‐state structure of 5 gives evidence of ligand exchange as a scenario that might be favored over oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…For further comparison, it has been previously shown that the alkylaluminate complex [(C 5 Me 5 ) 2 Y(AlMe 4 )] activates benzene and toluene forming phenyl-incorporated heteroaluminato moieties, which can be displaced by a donor solvent like THF. [45] Although we did not succeed in fully characterizing compound 5, mainly because NMR spectroscopy was not definitive due to the paramagnetic nature of divalent samarium, the solid-state structure of 5 gives evidence of ligand exchange as a scenario that might be favored over oxidation. Although one would generally assume that samarium(II) complexes should be easier to oxidize according to its more negative reduction potential, in some cases ytterbium(II) complexes get faster oxidized, whereas samarium congeners require a certain induction period.…”
Section: Methodsmentioning
confidence: 98%
“…Weiterhin wurde bereits gezeigt dass der Alkylaluminat‐Komplex (C 5 Me 5 ) 2 Y(AlMe 4 ) Benzol und Toluol unter Bildung von Phenylheteroaluminato‐Einheiten aktiviert, die durch ein Donorlösungsmittel wie THF verdrängt werden können [45] . Obwohl es uns nicht gelungen ist, Komplex 5 vollständig zu charakterisieren, insbesondere da die NMR‐Spektroskopie aufgrund der paramagnetischen Natur des zweiwertigen Samariums nicht aussagekräftig war, zeigt 5 , dass Ligandenaustausch ein Szenario darstellt, was gegenüber der Oxidation bevorzugt sein kann.…”
Section: Ergebnisse Und Diskussionunclassified
“…Weiterhin wurde bereits gezeigt dass der Alkylaluminat-Komplex (C 5 Me 5 ) 2 Y(AlMe 4 ) Benzol und Toluol unter Bildung von Phenylheteroaluminato-Einheiten aktiviert, die durch ein Donorlösungsmittel wie THF verdrängt werden können. [45] Obwohl es uns nicht gelungen ist, Komplex 5 vollständig zu charakterisieren, insbesondere da die NMR-Spektroskopie aufgrund der paramagnetischen Natur des zweiwertigen Samariums nicht aussagekräftig war, zeigt 5, dass Ligandenaustausch ein Szenario darstellt, was gegenüber der Oxidation bevorzugt sein kann. Obwohl man im Allgemeinen aufgrund des negativeren Redoxpotentials davon ausgehen würde, dass Samarium(II)-Komplexe leichter oxidierbar sein sollten, werden Ytterbium(II)-Komplexe in einigen Fällen schneller oxidiert, wohingegen entsprechende Samarium-Verbindungen einer gewissen Induktionsperiode bedürfen.…”
Section: Synthese Und Kristallstruktur Zweiwertiger Lanthanoid-tetrai...unclassified
“…3 The rare-earth-metal methyl complexes, most likely potential precursors for terminal LnCH 2 (CH) complexes, 4 have remained the focus of interest since Watson's report of a lutetium-terminal methyl complex in 1983. 7 a To date, in comparison with the well-studied methyl-bridged 5 and aluminate ligand stabilized terminal methyl complexes, 6 aluminum-free mononuclear terminal methyl complexes have been investigated far less, 7 which is mainly attributed to their thermodynamically poor stability, yielding multiple CH bond activations and the obvious tendency for oligomerization. In stark contrast, the chelating aminobenzyl coordinates with rare-earth-metals to form thermodynamically stable monomeric alkyl complexes, which can promote their reactivity investigations, such as rare-earth-metal aminobenzyl complexes which can be used as precursors for the preparation of other organo-rare-earth-metal derivatives 8 and catalysts for organic synthesis 9 and olefin polymerization.…”
Section: Introductionmentioning
confidence: 99%